Impact of Land-Use Change on Atmospheric Environment Using Refined Land Surface Properties in the Pearl River Delta, China - Anqi Lai; Yiming Liu; Xiaoyang Chen; Ming Chang; Qi Fan; Pakwai Chan; Xuemei Wang; Jianing Dai (Advances in Meteorology)
We replaced the outdated land-use of the Weather Research and Forecasting-Chemistry (WRF-Chem) model with a refined dataset, the Global Land Cover 2009 (GLC2009) dataset, to investigate the impact of land-use change on the regional atmospheric environment in the Pearl River Delta (PRD) region. Simulations of two months in 2014 (January and July) showed that land-use change increased the monthly averaged 2 m temperature by 0.24°C and 0.27°C in January and July, respectively. The relative humidity decreased by 2.02% and 2.23% in January and July, respectively. Due to the increase in ground roughness, the monthly averaged wind speed in January and July decreased by 0.19 m/s and 0.16 m/s. The planetary boundary layer height increased throughout the day and with larger relative increase during the nighttime. These subtle changes caused by land-use resulted in discernable changes in pollutant concentrations. Monthly averaged surface O3 concentration increased by 0.93 µg/m3 and 1.61 µg/m3 in January and July, while PM2.5 concentration decreased by 1.58 µg/m3 and 3.76 µg/m3, and the changes in pollutant concentrations were more noticeable during the nighttime. Overall, the impacts of land-use change on the atmospheric environment are obvious throughout the PRD region, especially in the urbanized areas.